Sun Protection of Rice, Gac Fruit and Wood Apple Powders for Developing Face Powder - Senajuk, Watchara; Phasuk, Sasamol; Nilsang, Poonyanuch; Takolpuckdee, Pannraphat (Journal of Food Health and Bioenvironmental Science, 2023)
Face powder, in different colors, is used to beautify the skin of the face and neck and make it appear more attractive than natural skin. General characteristics are that it should be fine, soft, easily applied to the skin, long-lasting, disperse well when moist and able to hide wrinkles or dark spots; further, in harmony with the skin color, it should reduce oiliness, have a pleasant smell or color, look natural and not harm the user. We studied the effect of gac fruit and wood apple on color and SPF in face powder containing rice. We examine the natural contents of rice, gac fruit and wood apple in face powder according to the percentage of each recipe. However, the natural extracts were able to absorb UV radiation and used in mixtures with synthetic extracts for sunscreen protection, thus reducing the use of synthetic products. Further, no heavy metals were found in the natural extracts.